2022
DOI: 10.1200/op.21.00750
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Telemedicine Use at a Northern New England Cancer Center During the COVID-19 Pandemic

Abstract: PURPOSE: To characterize the use of telemedicine for oncology care over the course of the COVID-19 pandemic in Northern New England with a focus on factors affecting trends. METHODS: We performed a retrospective observational study using patient visit data from electronic health records from hematology-oncology and radiation-oncology service lines spanning the local onset of the pandemic from March 18, 2020, through March 31, 2021. This period was subdivided into four phases designated as lockdown, transition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…We conducted 11/20 (55%) provider, 3/20 (15%) leader, and 6/20 (30%) staff interviews ( Table 2 ). All providers reported adopting some form of telemedicine for a significant proportion of visits in the early months of the pandemic (March-June 2020), predominantly via phone (vs video), consistent with our prior quantitative analysis [ 24 ]. Telemedicine use (video and phone combined) by the providers in this sample also mirrored that of the entire DCC oncology service, which peaked at an average weekly telehealth visit rate of 26% of visits in the initial lockdown phase, settling out to an average of 10%-12% after lockdown [ 23 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We conducted 11/20 (55%) provider, 3/20 (15%) leader, and 6/20 (30%) staff interviews ( Table 2 ). All providers reported adopting some form of telemedicine for a significant proportion of visits in the early months of the pandemic (March-June 2020), predominantly via phone (vs video), consistent with our prior quantitative analysis [ 24 ]. Telemedicine use (video and phone combined) by the providers in this sample also mirrored that of the entire DCC oncology service, which peaked at an average weekly telehealth visit rate of 26% of visits in the initial lockdown phase, settling out to an average of 10%-12% after lockdown [ 23 ].…”
Section: Resultssupporting
confidence: 80%
“…Quantitative analysis of telemedicine use (including the use of either telephone or video to provide real-time care similar to an in-person office visit) within the DCC over a 1-year time frame from pandemic onset revealed relatively low use compared to other specialties [ 23 ], and further analysis showed significant variability in use by clinic site corresponding to a larger magnitude of difference in telemedicine use rates compared with patient, geographic, or medical factors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that physician specialty, patient volume, practicing at multiple locations, and practicing at the hub hospital were associated with telehealth use, but the strength of these associations differed across cancer types. Our study also corroborates recent work that found that variation across practices and clinicians explains a substantial amount of the variance in telehealth use [ 25 , 26 ]. Interestingly, we observed that patient encounters with oncologists who practice at more than 1 location were less likely to occur via telehealth.…”
Section: Discussionsupporting
confidence: 91%
“…For example, despite the widespread utilization of telemedicine during the pandemic, 20 controversy still remains regarding the ideal setting for this care delivery strategy, especially when it comes to high-risk patients with cancer. 12,17,[21][22][23] Work by Tevaarwerk et al analyzing survey responses from 1038 oncologists found that whereas most oncologists felt favorably toward incorporating telemedicine into some aspects of their patient care, clinical scenarios requiring patient-provider connection were better served by an in-person visit. 13 Likewise, Stavrou et al found that of 71 breast medical oncologists, 74% felt in-person visits better facilitate connection with patients and 63% felt they improve the quality of communication.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of telemedicine into the clinical workflow for this patient population presents several obstacles; however, quantifying its impact on key components of cancer care, such as rates of advance care planning and acute care utilization, would help guide efforts to improve telemedicine implementation. For example, despite the widespread utilization of telemedicine during the pandemic, 20 controversy still remains regarding the ideal setting for this care delivery strategy, especially when it comes to high‐risk patients with cancer 12,17,21–23 . Work by Tevaarwerk et al.…”
Section: Introductionmentioning
confidence: 99%